2010
DOI: 10.1051/dst/2009052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk pasteurization and curd scalding temperature on proteolysis in Malatya, a Halloumi-type cheese

Abstract: -The effect of pasteurization of cheese milk and cooking temperature of the curd on proteolysis of Malatya cheese was examined during ripening. The cheeses that were characterized by the scalding of curd in hot whey were manufactured from raw or pasteurized milk and the curds were scalded in hot whey at 60, 70, 80 or 90°C. Differences in the levels of pH 4.6-soluble nitrogen between cheeses were significant (P < 0.05) after 30 days of ripening. Urea-polyacrylamide gel electrophoresis of the pH 4.6-insoluble fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Major steps in cheese manufacture include Tyr-Pro-Phe-Pro-Gly-Pro-Ile-Pro-Asn-Ser-Leu Kaminski et al (2007) FORMATION, DEGRADATION OF BETA-CASOMORPHINS IN DAIRY PROCESSING heat treatment of milk, coagulation with rennet and starter culture, separation of curd from whey, and ripening of curd to produce the final cheese. Heat treatment of milk is commonly done by pasteurization at 72 C for 15 seconds (Hayaloglu et al, 2010). Cheese studies that used milk heated at above 72 C involving peptide profiles (Hougaard et al, 2010) showed denaturation of whey protein, leading to the interaction between whey protein and casein.…”
Section: Cheesementioning
confidence: 99%
See 4 more Smart Citations
“…Major steps in cheese manufacture include Tyr-Pro-Phe-Pro-Gly-Pro-Ile-Pro-Asn-Ser-Leu Kaminski et al (2007) FORMATION, DEGRADATION OF BETA-CASOMORPHINS IN DAIRY PROCESSING heat treatment of milk, coagulation with rennet and starter culture, separation of curd from whey, and ripening of curd to produce the final cheese. Heat treatment of milk is commonly done by pasteurization at 72 C for 15 seconds (Hayaloglu et al, 2010). Cheese studies that used milk heated at above 72 C involving peptide profiles (Hougaard et al, 2010) showed denaturation of whey protein, leading to the interaction between whey protein and casein.…”
Section: Cheesementioning
confidence: 99%
“…However, the endogenous protease plasmin has been shown not to release BCMs (Gaucher et al, 2008) and similarly the rennet enzymes used to coagulate milk protein also do not liberate bioactive peptides (McSweeney, 2004); excluding these enzymes activities as sources of BCMs. Hayaloglu et al (2010) investigated the peptide profile of Malatya cheese made from raw milk without addition of starter culture. The authors demonstrated considerably higher concentration of peptides but did not measure BCMs, although they may have been present in this cheese.…”
Section: Cheesementioning
confidence: 99%
See 3 more Smart Citations